Mixed convection analysis in trapezoidal cavity with a moving lid - Mamun, M.A.H.; Tanim, T.R.; Rahman, M.M.; Saidur, Rahman; Nagata, S. (International Journal of Mechanical and Materials Engineering, 2010)
Mixed convection heat transfers in a two-dimensional trapezoidal cavity with constant heat flux at the heated bottom wall while the isothermal moving top wall in the horizontal direction has been studied numerically. Control Volume based finite volume method (FVM) has been used to discretize the governing differential equations. The pressure- velocity coupling in the governing equations is achieved by using the well known SIMPLE method for numerical computations. A second order upwind differencing scheme is to be used for the formulation of the coefficients in the finite-volume equations. All computations are to be done for a range of Richardson number, Ri from 0.1 to 10 and the aspect ratio, A are to be changed from 0.5 to 2 for a fluid having Prandtl number equal to 0.71 (air). First the optimum configuration of the trapezoidal cavity has been obtained by changing the inclination angle, Î³ of the side walls. Then the effect of Richardson number, aspect ratio, and Rotation angle, Ï (30deg;, 45Â° and 60Â°) of the optimum trapezoidal cavity has been studied by changing the desired parameter. Results have been presented in the form of streamline and isotherm plots as well as the variation of the Nusselt number at the heat source surface under different conditions. The results shows that with increasing Ri, the heat transfer rate increases as natural convection dominates. The rotational angle of the trapezoidal cavity and the direction of the lid motion affect the heat transfer rate significantly. Optimum heat transfer rate is obtained at aiding flow condition having higher values of Ri.